2012
DOI: 10.1073/pnas.1201890109
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of a protosynaptic gene expression network

Abstract: Assembly of a functioning neuronal synapse requires the precisely coordinated synthesis of many proteins. To understand the evolution of this complex cellular machine, we tracked the developmental expression patterns of a core set of conserved synaptic genes across a representative sampling of the animal kingdom. Coregulation, as measured by correlation of gene expression over development, showed a marked increase as functional nervous systems emerged. In the earliest branching animal phyla (Porifera), in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 42 publications
3
66
3
1
Order By: Relevance
“…But knowing whether PSD genes occur and function together in sponges would help determine when components of a proper PSD arose. In this vein, correlation analysis by Conaco et al (Conaco et al, 2012) suggested that although there is a lack of global coregulation of the entire set of PSD genes, small modules are coexpressed. But there is some circularity in this reasoning, because the same analysis suggests there is no co-regulation of epithelial genes in sponges based on the fact that the authors did not consider sponges to possess proper epithelia.…”
Section: Conducting Pathways and Effectorsmentioning
confidence: 99%
“…But knowing whether PSD genes occur and function together in sponges would help determine when components of a proper PSD arose. In this vein, correlation analysis by Conaco et al (Conaco et al, 2012) suggested that although there is a lack of global coregulation of the entire set of PSD genes, small modules are coexpressed. But there is some circularity in this reasoning, because the same analysis suggests there is no co-regulation of epithelial genes in sponges based on the fact that the authors did not consider sponges to possess proper epithelia.…”
Section: Conducting Pathways and Effectorsmentioning
confidence: 99%
“…For example, γ-aminobutyric acid (GABA), glutamate and nitric oxide (NO) have all been detected in sponges and shown to regulate cell behavior (Ellwanger et al, 2007;Elliott and Leys, 2010). A recent transcriptome profiling of the sponge A. queenslandica revealed the expression of wide repertoire of components active in synapses found in the vertebrate nervous systems (Conaco et al, 2012). In the social amoeba Dictysotelium, disruption of a glutamate receptor by homologous recombination reveals a role for glutamate signaling in the suppression of cell division (Taniura et al, 2006), while GABA induces terminal differentiation of spores through a GABA B receptor (Anjard and Loomis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mh, In the last decade, extensive research on complexity in networks has evidenced (among many results [1, 2]) the widespread of modular structures and the importance of quasi-independent communities in many research areas such as neuroscience [3,4], biochemistry [5] and genetics [6], just to cite a few. In particular, the modular, hierarchical architecture of cortical neural networks has nowadays been analyzed in depths [7], yet the beauty revealed by this investigation is not captured by the statistical mechanics of neural networks, nor standard ones (i.e.…”
mentioning
confidence: 99%